2016
DOI: 10.1159/000446344
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Colorectal Cancer Patients Under the Age of 50: Recent Experience and Case-Control Study of Prognosis in a Japanese Cohort

Abstract: Background/Aims: The incidence of colorectal cancer (CRC) in young people is increasing, indicating an urgent need for understanding young-onset CRC. This study serves to clarify the characteristics and prognosis of young CRC patients. Methods: Using a detailed database, various clinicopathological findings including symptoms, family history and prognosis of 70 young CRC patients under 50 years who underwent surgical resection between 2005 and 2011 were compared to 786 old CRC patients over 50 years. For the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…This propensity of left-sided colon and rectal cancers in the younger population has been described in some other studies. [25][26][27] A recent study of 739 CRC patients < 50 years showed that most had tumors of left side (83%) compared to right side (17%). 28 Studies have also shown that the tumors of rectum and left-sided colon are associated with increased survival compared to right-sided CRC, which is the result of the different embryologic origin of these parts of the gut.…”
Section: Discussionmentioning
confidence: 99%
“…This propensity of left-sided colon and rectal cancers in the younger population has been described in some other studies. [25][26][27] A recent study of 739 CRC patients < 50 years showed that most had tumors of left side (83%) compared to right side (17%). 28 Studies have also shown that the tumors of rectum and left-sided colon are associated with increased survival compared to right-sided CRC, which is the result of the different embryologic origin of these parts of the gut.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of young-onset CRC in developing countries were noted to be higher than those in developed countries. (8)(9)(10)(11)16,18,19,22,23) This puzzling difference may be due to lifestyle and dietary patterns that individuals are exposed to during their childhood and younger adulthood years, which were different from those of preceding generations. (24) In other words, in historically low-risk regions for CRC, where rates in the older population have remained low, CRC incidence has increased significantly in newer generations.…”
Section: Discussionmentioning
confidence: 99%
“…The clinicopathological characteristics described in this study are in keeping with the current understanding of young-onset CRC, which usually presents with altered bowel habit and per-rectal bleeding. (9)(10)(11)14) The diagnostic challenge here is to distinguish benign causes of per-rectal bleeding from malignant causes. It is challenging for clinicians to thoroughly investigate per-rectal bleeding among young adults owing to cost constraints in public hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of rectal cancers is higher among adults under 50910 than in older adults. In the US, colorectal cancer is not only increasing among under 50s but presenting at later stages11; thus, the evidence suggests a real increase of aggressive disease arising at younger ages.…”
Section: Patterns Of Changementioning
confidence: 93%